Experimental Study on Shear Behavior and Failure Mechanism of Bolted Heterogeneous Rock Joints under Different Anchorage Conditions - Xianzhen Cheng; Hengjie Luan; Yujing Jiang; Sunhao Zhang; Chuanyang Jia (Geofluids)
Despite their frequent natural occurrence and engineering encounter, heterogeneous rock joints (rock joints with different lithological characters on both sides of the joint surface) have been studied much less systematically. To study the shear behavior and failure mechanism of bolted heterogeneous rock joints, laboratory tests were performed on the heterogeneous rock joints having different joint roughness coefficients (JRC) under different anchorage conditions. The results indicate that shear strength increases with the increase of JRC, showing exponential growth. Under the same roughness, the shear strengths of rock joints from large to small are fully grouted, end anchorage, and without anchorage. The mechanical characteristics of the bolt and joint are poorly matched under the end anchorage condition, which is easy to cause these two to be broken one by one. Under fully grouted, the extrusion force caused by the rock bolt will diffuse around the anchorage agent and will not cause partial continuous damage. The surface damage of heterogeneous rock joints increases with the increase of JRC and presents obvious heterogeneous characteristics. The shear dislocation between the blocks under shear load results in the interaction between the bolt and surrounding media. Under the action of shear force, the bolt body produced both axial and transverse deformation, which leads to breakage of anchorage agent and rock mass. Rock bolt has a significant impact on the shear behavior of the anchorage system, and the damage of the rock bolt to rock mass should be considered in rock engineering reinforcement design.